The Relationship/Association of Triglyceride and Severity of Coronary Artery Disease: Is Triglyceride Really a Risk Factor for Coronary Artery Disease? - Karmoker, Kajal Kumar; Siddika, Khandaker Aisha; Rahman, Mohammad Walidur; Datta, Bijoy; Rashid, Mohammad Bazlur; Mallick, Golam Rahman; Sana, Niranjan Kumar (University Heart Journal, 2022)
Worldwide, the major cause of mortality and morbidity is coronary artery disease (CAD). In the pathogenesis and progression of atherosclerosis, lipid and its metabolites play an important role. The aim of the study was to find out the association of triglyceride (TG) level on the severity of coronary artery disease (CAD) in patients with ischemic heart disease (IHD). In this cross-sectional study, 431 patients with ischemic heart disease were enrolled after taking informed written consent. TG level were categorized into normal (< 150 mg/dl), borderline (150-199 mg/dl) and high (³200 mg/dl). Patients with ischemic heart disease (IHD) were stratified according to TG level. Severity of CAD was assessed by the Gensini score. Most of the patients (33.4%) belonged to the age group 51–60 years. The mean age was 51.31±10.30 years. The majority (74.5%) of patients were male. Among risk factors, 205 (47.6%) patients were smokers, followed by hypertension 190 (44.1%) and diabetes mellitus 175 (40.5%). The association of TG with the whole spectrum of IHD was found statistically significant (p < 0.05). Moderate to severe CAD was found to be higher in the high TG level group compared with the other groups and was statistically significant. University Heart Journal 2022; 18(2): 101-105